2021
DOI: 10.1093/rheumatology/keab268
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of anti-melanoma differentiation associated gene 5 (MDA5) IgG subclasses in MDA5+ dermatomyositis

Abstract: Objectives The anti-melanoma differentiation-associated gene 5 (MDA5) antibody is the main predictor of interstitial lung disease (ILD) in dermatomyositis (DM) and clinically amyopathic dermatomyositis (CADM). Nevertheless, a subset of MDA5+ patients have a favorable prognosis. We aimed to determine the possibility of using anti-MDA5 antibody isotypes and IgG subclasses for evaluating ILD risk. Methods The isotypes (IgG, IgA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Interestingly, anti-MDA5 IgG1 were associated with higher serum ferritin levels, severe interstitial pneumonia, and a higher mortality rate. The combined positivity for anti-MDA5 IgG1 and anti-MDA5 IgG4 was predictive of poor prognosis ( 145 ). IgG1 are potent activators of the complement pathway, and as a result, anti-MDA5 IgG1 could be the main subclass involved in the pathogenesis of the disease.…”
Section: Pathogenesis Of the Diseasementioning
confidence: 99%
“…Interestingly, anti-MDA5 IgG1 were associated with higher serum ferritin levels, severe interstitial pneumonia, and a higher mortality rate. The combined positivity for anti-MDA5 IgG1 and anti-MDA5 IgG4 was predictive of poor prognosis ( 145 ). IgG1 are potent activators of the complement pathway, and as a result, anti-MDA5 IgG1 could be the main subclass involved in the pathogenesis of the disease.…”
Section: Pathogenesis Of the Diseasementioning
confidence: 99%
“…One study showed that DM/CADM patients with anti-MDA5 IgG1 subclasses were correlated to significantly higher occurrence rates of acute interstitial pneumonia, serum levels of lactate dehydrogenase (LDH), and ferritin. Higher mortality rates were detected in patients who were positive for anti-MDA5 IgG1 and IgG4, thus suggesting that these two IgG subtypes might serve as useful biomarkers for predicting mortality in patients with DM-ILD ( 74 ).…”
Section: The Mechanisms Underlying Ifn I Pathway In Mda5 + Dmmentioning
confidence: 99%
“…A fluorescein isothiocyanate (FITC)-conjugated goat anti-human IgG,A,M antibody (BI2114; Abliance, Compiègne, France) was diluted at 1:300 in PBS and used as a secondary Ab, which was contrary to the ELISA method that uses an anti-IgG only. The choice of using anti-IgG,A,M Abs, rather than anti-IgG Abs as secondary Abs in the IIF test, is justified by the fact that it has previously been reported that different isotypes of anti-MDA5 antibodies are detectable in the serum of patients, including the different subtypes of IgG, IgA, and IgM [ 27 ]. Moreover, the FITC anti-IgG,A,M Abs used in this study did not generate disturbing background noise for reading.…”
Section: Methodsmentioning
confidence: 99%